Meningkatkan Mutu Pendidikan Melalui Kepemimpinan - Cindy Mutiara Wati Mulaicin; Ismatul Hawa; Khodijah Ghinaa Amini; Nurvinayani, Nurvinayani (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
Effective management in curriculum administration requires the role of teachers as professional educators. This role is not only focused on interactions in the classroom, but also includes other important aspects in the world of education. As class leaders, teachers have a great responsibility in designing and managing the teaching process, from compiling learning programs to implementing appropriate evaluation strategies. The quality of education is also greatly influenced by school leadership that is able to design strategies to improve the quality of learning, with the involvement of all elements in the school. In this context, visionary leadership is the key to building a quality learning system, where there is synergy between educators, the community, and schools as the main supporting factors in creating an effective educational environment.